2017
DOI: 10.1080/00071668.2017.1390213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA methylation and transcriptional regulatory regions in the promoter of duck retinoic acid inducible gene I (RIG-I)

Abstract: 1. The aim of this study was to identify the active control area of the duck retinoic acid-inducible gene I (duRIG-I) core promoter, to predict the binding sites of transcription factors and to provide a theoretical basis for the study of duRIG-I function and mechanism of regulation. 2. The promoter region of duRIG-I was obtained from Ensembl; the CpG island in the duRIG-I promoter was predicted online; and the methylation status of the duRIG-I promoter was detected by the bisulphite sequencing PCR method. 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The CpG context is highly methylated, while most CpG islands are not methylated, which means that CpG islands in the promoter region can be methylated, resulting in the inhibition of gene expression [ 19 22 ]. The gene expression of RIG-I and MDA5 is also regulated by the methylation level of CpG islands in the promoter region of the coding genes [ 23 , 24 ]. The methylation level of CpG islands can reflect the expression of RIG-I and MDA5 and indirectly reflect the antiviral effect [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CpG context is highly methylated, while most CpG islands are not methylated, which means that CpG islands in the promoter region can be methylated, resulting in the inhibition of gene expression [ 19 22 ]. The gene expression of RIG-I and MDA5 is also regulated by the methylation level of CpG islands in the promoter region of the coding genes [ 23 , 24 ]. The methylation level of CpG islands can reflect the expression of RIG-I and MDA5 and indirectly reflect the antiviral effect [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression of RIG-I and MDA5 is also regulated by the methylation level of CpG islands in the promoter region of the coding genes [ 23 , 24 ]. The methylation level of CpG islands can reflect the expression of RIG-I and MDA5 and indirectly reflect the antiviral effect [ 23 ]. Zhang et al found that the methylation level of the chicken genome was significantly upregulated after infection with H5N1 avian influenza virus [ 25 ].…”
Section: Introductionmentioning
confidence: 99%